Pengaruh Jenis dan Ketebalan Karbon Aktif pada Sistem Constructed Wetlands untuk Pengolahan Limbah Cair Rumah Tangga - Anton Kuswoyo; Almira Ulimaz (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The main environmental problem today is still about pollution. Residential settlements always produce waste, especially household liquid waste. This type of waste is generally in the form of water that is cloudy in color and emits an unpleasant odor. This type of liquid waste is known as greywater. The direct impact of pollution is the contamination of groundwater (wells) and river water by greywater. As a result, the quality of the environment is getting disturbed. Especially in Angsau Village, Pelaihari Sub-district, Tanah Laut Regency, the majority of the population uses well water for bathing and washing toilets (MCK) and cooking. The purpose of this research is to reduce phosphate levels in greywater wastewater more effectively and efficiently. This type of research is a true experiment with a pretest-posttest research design with a control group design. The subject of the research was household liquid waste (greywater) which was taken at random in Angsau Village, Pelaihari District, Tanah Laut Regency, South Kalimantan Province. The study was designed with 6 treatments, namely variations of activated carbon used in two constructed wetlands reactor tanks. The first reactor uses coconut shell activated carbon, and the second reactor uses palm shell activated carbon. The results showed that, the thicker the activated carbon applied to the constructed wetlands reactor system, the lower the phosphate levels in household wastewater (greywater). The highest average percentage value was in the treatment with 15 cm thick activated carbon, and the lowest percentage mean value was in the treatment with 5 cm thick activated carbon. The results also showed that activated carbon from palm shells was more effective in reducing phosphate levels in household wastewater (greywater) compared to the use of activated carbon from coconut shells.